1995
DOI: 10.1104/pp.109.4.1461
|View full text |Cite
|
Sign up to set email alerts
|

Suborganellar Localization and Molecular Characterization of Nonproteolytic Degraded Leukoplast Pyruvate Kinase from Developing Castor Oil Seeds

Abstract: Plastid pyruvate kinase (PK,) activity and anti-(castor oil seed [COSI PK, ) immunoglobulin C immunoreactive polypeptides were recovered in the stroma but not from envelope membranes of purified COS leukoplasts that had been subfractionated by sucrose density gradient centrifugation. The PK, was highly purified from isolated leukoplasts using anion-exchange and ADP-agarose chromatographies. Proteolysis of PK, was almost entirely eliminated by including 2,2'-dipyridyl disulfide in purification buffers. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 30 publications
1
27
0
3
Order By: Relevance
“…This step is considered to be a highly regulated glycolytic step as it is activated by pH changes, inhibited by Glu/Asp and ATP, and degraded after phosphorylation and ubiquitination (Podesta and Plaxton, 1991;Tang et al, 2003;Turner et al, 2005). Among the oilseeds compared, PK c isoforms were identified in soybean and castor, while the PK p was identified in rapeseed; however, in earlier studies, PK p activity and concentration was shown to coincide with fatty acid levels in developing castor seed (Plaxton, 1991;Negm et al, 1995). Castor and soybean expression patterns are very different.…”
Section: Five Glycolytic Proteins Showed An Increased Number Of Isofomentioning
confidence: 94%
“…This step is considered to be a highly regulated glycolytic step as it is activated by pH changes, inhibited by Glu/Asp and ATP, and degraded after phosphorylation and ubiquitination (Podesta and Plaxton, 1991;Tang et al, 2003;Turner et al, 2005). Among the oilseeds compared, PK c isoforms were identified in soybean and castor, while the PK p was identified in rapeseed; however, in earlier studies, PK p activity and concentration was shown to coincide with fatty acid levels in developing castor seed (Plaxton, 1991;Negm et al, 1995). Castor and soybean expression patterns are very different.…”
Section: Five Glycolytic Proteins Showed An Increased Number Of Isofomentioning
confidence: 94%
“…The reconstitution of active PK p s from individually purified inactive subunits in this study and the in vivo co-IP results leave little ambiguity as to the heteromeric structure of the Arabidopsis PK p s. Some studies of recombinant PK p polypeptides from developing R. communis endosperm concluded that the PK p -a and PK p -b homologs are distinct enzymes (Blakeley and Dennis, 1993;Blakeley et al, 1995;Wan et al, 1995), while others have determined that the same proteins are actually subunits of a single heteromeric PK p complex (Plaxton et al, 1990;Plaxton, 1991;Negm et al, 1995). The data presented in this article support the conclusion that PK p is a complex composed of two different subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis, for instance, has 14 annotated PK genes that likely exhibit a large degree of variation with respect to regulation of gene expression and enzyme activity (Arabidopsis Genome Initiative, 2000). PK p has been purified and characterized from castor (Ricinus communis) endosperm and B. napus suspension cell cultures (Plaxton et al, 1990Negm et al, 1995). Both enzymes consist of a-and b-subunits and appear to exist as 3a3b heterohexamers.…”
Section: Introductionmentioning
confidence: 99%
“…The endosperm and embryo of castor seeds at stages 5 to 7 (Greenwood and Bewley, 1981) were excised and the leucoplasts isolated according to the method of Negm et al (1995). Protease inhibitors were omitted from the buffers.…”
Section: Plant Materials and Leucoplast Lsolationmentioning
confidence: 99%
“…Leucoplasts were isolated from developing castor endosperm as described by Negm et al (1995). This method has been shown to yield highly intact leucoplast preparations, which are devoid of contamination from the cytosol and other subcellular compartments (Negm et al, 1995).…”
Section: The Uptake Of Malate and Pyruvate By Lsolated Leucoplastsmentioning
confidence: 99%